The clinicopathological significances and related signal pathways of BTG3 mRNA expression in cancers: A bioinformatics analysis - Zheng, Hua-Chuan; Xue, Hang; Zhang, Cong-Yu; Shi, Kai-Hang; Zhang, Rui (Frontiers in Genetics, 2022)
BTG3 is reported to be a tumor suppressor and suppresses proliferation and cell cycle progression. This study aims to analyze BTG3 mRNA expression in human beings through bioinformatics analysis. We analyzed Oncomine, TCGA, Xiantao, UALCAN and KM plotter databases by student t-test, log-rank statistic, Cox’s proportional hazards model, and KEGG analysis. Down-regulated BTG3 expression was observed in lung and breast cancers, compared with normal tissues (p<0.05), but not for gastric and ovarian cancer (p<0.05). The methylation of BTG3 was shown to be adversely correlated with its mRNA expression (p<0.05). BTG3 expression was higher in gastric intestinal-type than diffuse-type, and Grade 1 than G3 carcinomas (p<0.05), in female than male cancer patients, T1-2 than T3-4, and adenocarcinoma than squamous cell carcinoma of lung cancer (p<0.05), in invasive ductal than lobular carcinoma, N0 than N1 and N3, TNBC than luminal and Her2+, and Her2+ than Luminal cancer of breast cancer (p<0.05), and in G3 than G2 ovarian carcinoma (p<0.05). BTG3 expression was positively related to the survival rate of gastric and ovarian cancer patients (p<0.05), but not for breast cancer (p<0.05). KEGG and PPI analysis showed that the BTG3 was involved in cell cycle and DNA replication, digestin and absorption of fat and protein, and spliceosome and ribosome in cancer. BTG3 overexpression was positively linked to carcinogenesis, histogenesis, and aggressive behaviors, and was employed to evaluate the prognosis of cancers.